2017
DOI: 10.1007/s10096-017-3044-2
|View full text |Cite
|
Sign up to set email alerts
|

agr functionality affects clinical outcomes in patients with persistent methicillin-resistant Staphylococcus aureus bacteraemia

Abstract: Methicillin-resistant Staphylococcus aureus bacteremia (MRSAB) often persists despite appropriate antibiotic therapy. It is unclear what microbiological factors contribute to poor clinical outcomes in persistent MRSAB (pMRSAB). We aimed to identify clinical and microbiological risk factors for in-hospital mortality in pMRSAB. We analysed MRSAB cases prospectively collected between 2009 and 2016 at 11 hospitals in Korea, defining cases of pMRSAB as MRSAB lasting ≥5 days despite administration of effective antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…To date, many studies have analysed the association between agr dysfunction and poor clinical outcomes of invasive S. aureus infection in various clinical settings 30,32,43,44,49,50 . Since Schweizer et al reported that SAB with dysfunctional agr was associated with excessive mortality among severely ill patients 29 , subsequent studies have demonstrated that agr dysfunction was associated with higher mortality 31,32 , and the persistence of bacteraemia www.nature.com/scientificreports/ in patients with SAB, especially in MRSA bacteraemia 7,30 . However, some studies reported that agr dysfunction of MRSA bacteraemia was not associated with treatment failure 39,41,42 , or mortality 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies have analysed the association between agr dysfunction and poor clinical outcomes of invasive S. aureus infection in various clinical settings 30,32,43,44,49,50 . Since Schweizer et al reported that SAB with dysfunctional agr was associated with excessive mortality among severely ill patients 29 , subsequent studies have demonstrated that agr dysfunction was associated with higher mortality 31,32 , and the persistence of bacteraemia www.nature.com/scientificreports/ in patients with SAB, especially in MRSA bacteraemia 7,30 . However, some studies reported that agr dysfunction of MRSA bacteraemia was not associated with treatment failure 39,41,42 , or mortality 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a possible intrinsic survival advantage of dysfunctional agr under vancomycin selective pressure [65][66][67] . However, most studies that used vancomycin as the main therapeutic agent showed a significant association between agr dysfunction and unfavourable outcomes regardless of vancomycin MIC [29][30][31][32] . Therefore, dysfunctional agr might be a marker of poor clinical outcomes of MRSA bacteraemia regardless of vancomycin MICs of causative organisms when patients were treated with vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its importance, several studies have focused on developing anti-Agr strategies in S. aureus , and obvious repression of pathogenicity has been confirmed ( Gray et al, 2013 ; Murray et al, 2014 ; Khan et al, 2015 ). However, though anti-Agr strategies seem promising, many groups have reported that Agr dysfunction promotes persistent bacteremia ( Fowler et al, 2004 ; Park et al, 2013 ; Kang et al, 2017 ), permits abscess formation ( Das et al, 2016 ), and increases mortality among patients with S. aureus bacteremia, especially the most severe cases ( Schweizer et al, 2011 ). The unexpected correlation of Agr dysfunction and worsened outcome of infection is intriguing and the reason remains unclear ( Painter et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Δ agr mutants, a higher biofilm production (Vuong et al, 2004; He et al, 2019) and higher degree of persister forms development, a phenotype associated with changed metabolism and resistance to many antibiotics (Xu et al, 2017), were observed (Figure 1). For Δ agr mutants, an increased tendency to initiate a chronic, difficult to eradicate bacteremia was also indicated (Fowler et al, 2004; Paulander et al, 2012; Park et al, 2013; Kang et al, 2017). He et al (2019) assessed the selective pressure associated with maintaining of the Agr activity in isolates from biofilm vs. non-biofilm staphylococcal infections.…”
Section: The Second Objection – the Reduction Of Virulence By Quorum mentioning
confidence: 99%